(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The debate surrounding the legal and constitutional standing of sex work in India is both complex and deeply rooted in societal, moral, and economic contexts. While trafficking for sexual exploitation is unequivocally condemned under Indian law, the question of whether consensual adult sex work can be treated as a legitimate form of livelihood remains unresolved in judicial and legislative spheres. This article critically examines the nuanced distinction between consensual adult sex work and trafficking within the Indian legal framework, with a focus on constitutional rights, statutory provisions, judicial interpretations, and evolving socio-legal perspectives. By analysing landmark judgments from the Supreme Court and various High Courts, this study explores how the judiciary has grappled with the competing imperatives of morality, public order, human rights, and personal autonomy. Furthermore, it assesses the effectiveness of laws like the Immoral Traffic (Prevention) Act, 1956 (ITPA), the Indian Penal Code,1860 (IPC), and relevant international conventions in addressing trafficking while safeguarding the rights of sex workers. The article concludes by identifying gaps in the current legal approach and proposing a balanced, rights-based framework that distinguishes consensual sex work from exploitation.